PENYESUAIAN DIRI REMAJA HAMIL DI LUAR NIKAH TERHADAP LINGKUNGAN SOSIALNYA : STUDI KASUS DI IDAMGAMLAMO, MALUKU UTARA - Greisilia Dengo; Tritjahjo Danny S. (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to understand the self-adjustment of adolescents who become pregnant outside of marriage towards family and social environment in Idamgamlamo Village, North Maluku. The phenomenon of teenage pregnancy out of wedlock in this area is a major concern due to the high number of cases and the significant impacts caused, both psychologically, socially and economically. This data was collected through in-depth interviews and observations, then analyzed qualitatively. The results showed that adolescent self-adjustment is strongly influenced by family support, acceptance of the social environment, as well as the individual's ability to manage emotions and build a positive self-concept. Adolescents who receive emotional and social support tend to be able to develop adaptive coping strategies, while those who experience rejection and discrimination are at risk of psychological and social disorders. The findings are expected to serve as a reference for parents, communities, and related parties to provide appropriate support and design effective interventions to help adolescents cope and adjust to the condition of pregnancy outside marriage.